Pompeii . . . buried alive! - Kunhardt, Edith (New York : Random House, 1987)
A simple retelling of the fateful days in A.D. 79 when mount Vesuvius erupted and the people in the ancient town Pompeii perished.
Keywords: Pompeii (Ancient city)-Juvenile literature; Vesuvius (Italy)-Eruption, 79-Juvenile literature